Renal actinomycosis presenting as a suppurated solitary cyst - Ioannis Efthimiou (Indian Journal of Urology, 2008)
We report the case of a middle-aged female with a solitary renal cyst suppurated by Actinomyces israeli . The patient was treated successfully by emergency nephrectomy. Based on a detailed negative history of inciting events and predisposing factors for actinomycosis, negative imaging modalities for extra-renal organ implication and no involvement of the surrounding renal parenchyma, the case is considered as primary renal actinomycosis affecting a solitary cyst of the kidney. This is the first such case reported in the international literature.